Long-term plastic mulching exacerbates the co-limitation of carbon and phosphorus in farmland by altering physicochemical properties and microbial interactions - Xu, Tong; Zheng, Shuang; Duo, Xinqu; Hou, Zhonghua; Wu, Jinggui (Frontiers in Microbiology, 2026)
Prolonged plastic film mulching causes plastic residue accumulation and microplastic (MP) formation, compromising soil structure and causing contamination. This study examined mulching duration effects (0, 5, 10, 15 years) on soil MPs, physicochemical properties, microbial communities, and nutrient limitations at 0–20 cm and 20–40 cm depths in maize soils of western Jilin, China. Mulching duration significantly increased MP abundance. Film-like MPs dominated, progressively fragmenting into smaller sizes over time. Long-term mulching enhanced soil moisture and EC (Electrical Conductivity) but decreased SOC (Soil Organic Carbon) and TN (Total Nitrogen), while increasing TP (Total Phosphorus) and AP (Available phosphorus). Microbial responses diverged: bacterial diversity and network complexity rose with enhanced cooperation, whereas fungal networks showed intensified competition. Extracellular enzyme stoichiometry indicated aggravated microbial co-limitation by C (Carbon) and P (Phosphorus), driven by MP-induced SOC depletion and altered P dynamics. SEM (Structural Equation Modeling) revealed that plastic mulching directly altered soil physicochemical properties through MPs accumulation, while indirectly regulating microbial community composition, ultimately exacerbating C-P co-limitation in microbial metabolism. The study highlights soil health risks from long-term mulching and highlights the necessity to seek alternatives such as biodegradable films to mitigate soil health risks associated with long-term plastic mulching.